Relationship between self-esteem, happiness and academic performance among children / Thiresyinie Tamil Chelvam and Nellie Ismail - Tamil Chelvam, Thiresyinie; Ismail, Nellie (Bahagian Penyelidikan dan Jaringan Industri, UiTM Cawangan Melaka, 2020)
This study aims to examine the relationship between self-esteem and happiness with academic performance among children. By using multi-stage cluster random sampling technique, 400 respondents were selected from two primary schools in Wilayah Persekutuan Kuala Lumpur. Self-Esteem Inventory and Subjective Happiness Scale were used to measure self-esteem and happiness respectively. Academic performance was measured by using the total percentage of marks obtained in the first test. The results showed that self-esteem and happiness have significant relationship with academic performance. Multiple regression analysis was used to analyze the relative strength of independent variables in predicting academic performance. The results indicated that self-esteem was found to have the strongest influence on children’s academic performance. This study concludes that children’s beliefs and feelings about themselves are a key determinant of academic success.